PERILAKU DEBITUR DALAM MENENTUKAN PEMBIAYAAN SYARIAH (STUDI PADA BPRS DI WILAYAH TANGERANG DAN BEKASI) - Hasnil Hasyim (Faculty of Economic and Business, 2012)
The aim of this study is to measure the preferences of debtor in shariah financing. Analysis method that used in this research is logit regression. Independent variables of this research are age, type of business, busines turnover, time, location, and value of financing. From the research it can be concluded that the debtor is engaged in the trade sektor, which has a turnover of approximately 20 – 50 millior/month, businesses located in the market, runs its business more than 2 years, borrowers who become customers of the bank for one year and the value of financing 10-25 million given to banks is more dominant in determining murabahah financing.DOI: 10.15408/etk.v11i1.1874